2017
DOI: 10.3389/fnmol.2017.00125
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Inhibition of Glycine Receptor Channels by Niflumic Acid

Abstract: Niflumic acid (NFA) is a member of the fenamate class of nonsteroidal anti-inflammatory drugs. This compound and its derivatives are used worldwide clinically for the relief of chronic and acute pain. NFA is also a commonly used blocker of voltage-gated chloride channels. Here we present evidence that NFA is an efficient blocker of chloride-permeable glycine receptors (GlyRs) with subunit heterogeneity of action. Using the whole-cell configuration of patch-clamp recordings and molecular modeling, we analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 81 publications
(108 reference statements)
1
26
0
1
Order By: Relevance
“…The voltage dependence of the inhibitory action of Azo‐NZ1 suggested that the compound might act as an open channel blocker of GABA A receptors (Maleeva, Peiretti, Zhorov, & Bregestovski, ). To test this hypothesis, we compared the action of Azo‐NZ1 at different concentrations of the agonist.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The voltage dependence of the inhibitory action of Azo‐NZ1 suggested that the compound might act as an open channel blocker of GABA A receptors (Maleeva, Peiretti, Zhorov, & Bregestovski, ). To test this hypothesis, we compared the action of Azo‐NZ1 at different concentrations of the agonist.…”
Section: Resultsmentioning
confidence: 99%
“…The 2′ residue of the TM2 domain (see Figure a) is a key region that determines the action of several pore blockers of Cys‐loop receptors, including cyanotriphenylborate (Rundström et al, ), picrotoxin (Lynch, Rajendra, Barry, & Schofield, ; Zhorov & Bregestovski, ), niflumic acid (Maleeva, Peiretti, Zhorov, & Bregestovski, ), and cyclothiazide (Xie, Song, Ripps, & Qian, ). The Azo‐NZ1 construct contains two features that are essential to impart sensitivity to the photochrome: (a) the negative charge of the sulphonate group (mimicking that of the chloride ion) and (b) the distance between this sulphonate group and the carbonyl group of the benzodiazepine core (see Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug and its derivatives are widely used in clinics for the relief of chronic and acute pain conditions [56]. Niflumic acid is also known as an inhibitor of several anion channels, including Ca ++ -activated [57-59] and swelling-activated [12] Cl - channels, and was reported to variably affect different membrane ion transport systems, such as anion exchangers [28, 60], the glycine [61], GABA(A) [62] and N-methyl-D-aspartate [63] receptors and T-type calcium channels [64]. The findings presented here show that 0.01-1 mM niflumic acid, despite being more potent on the swelling-activated Cl - current, also significantly blocked the K + current (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that NFA, a member of the fenamate class of non-steroidal anti-inflammatory drugs, is an efficient blocker of GlyRs with a subunit specificity of action ( Maleeva et al, 2017 ). At heterologous expression of the different GlyR subunits it has been shown that a blocking potency of NFA was about one order higher for alpha2 GlyRs than for the receptors formed by alpha1 subunits.…”
Section: Introductionmentioning
confidence: 99%